EVALUATION OF THE IMPACTS OF TRAINING ON EMPLOYEE PERFORMANCE IN THE UK HOTEL INDUSTRY: AN ANALYSIS OF EMPLOYEES’ PERSPECTIVES AT MARRIOTT INTERNATIONAL - Neupane, Ramesh; Khanal, Tantrika Raj (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this paper is to evaluate the impact of training on employee performance in the UK hotel industry. It has also analysed the effectiveness of employee performance, impacts of on-the-job training on employee performance, the impact of off-the-job training on employee performance, and the impact of online training on the performance of the employees of Marriott International hotels. This study was conducted based on the deductive approach and positivism philosophy. Three hypotheses were developed based on theory and literature. Primary data was collected from the employees who were participated in different types of training provided by Marriott International hotels. An online questionnaire survey through the Kwik Survey platform was used to collect primary data from the respondents. A sample of 172 employees was chosen through a voluntary response sampling technique. The data were analysed through SPSS using standard deviation, mean, correlation, regression, and charts. This study found that on-the-job training and off-the-job training have significant impacts on employee performance, while online training has no significant impact on employee performance. It is found that on-the-job training has a significant impact on employee performance as β = 0.846, and p = 0.000. Similarly, off-the-job training has a significant impact on employee performance as β = 0.572 and p = 0.26. And online training has no significant impact on employee performance as β = 0.301 and p = 0.276, which is more than 0.05. Similarly, evaluation of the mean of the scores for employee performance variables suggests that every variable of performance has a mean score of more than 3, and the mean score for overall employee performance is 4.03, which equals 80.6%. This means employee performance at Marriott International hotels based on employees’ own ratings is highly effective.